Pengaruh Kearifan Lokal terhadap Penerapan Sanksi Hukum Adat Atas Tindak Pidana yang Diatur oleh KUHP Terhadap Pelaku - Maulia Kuswicaksono (Jurnal Syntax Transformation, 2021)
The local wisdom of an area basically cannot be separated by the maintenance of community customs, where the stakeholders of Adat or the Head of Customs are those who have authority and are authorized (unwritten) by indigenous peoples to maintain and protect their customs. In the criminal law system in Indonesia, customary criminal law is a source of legal discovery whose existence is still highly recognized. This research aims to find out the influence of local wisdom on customary law sanctions for criminal acts regulated by the Criminal Code against behavior. By using descriptive analytical research methods, research data analysis is done initially through literature data. Obtained the result that the existence of customary criminal sanctions in the settlement of common criminal acts in Indonesia in the dasrnya still exists and is valid and in some areas the application of customary criminals becomes an alternative in the settlement of general criminal acts that are regulated and threatened as stipulated in the Criminal Code (Criminal Code), then customary criminal sanctions are actually recognized by the Judicial Institution, where against customary criminal convictions as customary reactions to perpetrators who when submitted to the trial to ask for criminal liability according to the Criminal Code are also unacceptable (Niet Ontvakelijk Verklaard).